Dignity and autonomy. Reflections about Kantian tradition - Gutmann, Thomas; Rendón Arroyave, Carlos (Estudios de Filosofía, 2019)
Kantian idea according to which only people can claim respect (“dignity”) and only for them can moral rights exist, yet, at the same time, not all human beings are people in this strict prescriptive sense, contains considerable potential of exclusion. From this view, the present article reconstructs the architecture of Kant’s moral philosophy (and of the Kantian tradition) and investigates thescope and the limits of the different proposals of solution based on his theory.